The Overview of Manufactured Systems Models - Tubychko, K.V.; Zaruba, V.Y.; Pignasty, O.M.; Khodusov, V.D. (Економічний вісник Донбасу, 2015)
The article provides an overview of the main models of manufacturing systems. Here a comparative analysis of different types of models and shows their applications. In this article A brief description of the main model parameters. The detailed analysis of the streaming models with the using of partial differential equations. In this article is their classification depending on the equation of state. We examined the cross-sectional and two-moment description of the production process.